2012
DOI: 10.1063/1.3673875
|View full text |Cite
|
Sign up to set email alerts
|

On the molecular structure of HOOO

Abstract: The molecular structure of trans, planar hydridotrioxygen (HOOO) has been examined by means of isotopic spectroscopy using Fourier transform microwave as well as microwave-millimeter-wave double resonance techniques, and high-level coupled cluster quantum-chemical calculations. Although this weakly bound molecule is readily observed in an electrical discharge of H(2)O and O(2) heavily diluted in an inert buffer gas, we find that HOOO can be produced with somewhat higher abundance using H(2) and O(2) as precurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 63 publications
7
61
0
Order By: Relevance
“…[24,25] More recently, Schreiner et al reported the generation of trans,trans-and trans,cis-HO À C À OH by the thermal extrusion of CO 2 from oxalic acid and its subsequent isolation in an argon matrix at 10 K. [23] A similar experiment showed that hydroxycarbene (HÀC ÀOH) rapidly isomerizes to formaldehyde (CH 2 O) at 10 K, a phenomenon attributed to quantum tunneling through the 125 kJ mol À1 ÀOH, with the CCSD(T)/cc-pVTZ relative energies calculated by Schreiner et al [23] barrier. The 5-43 GHz Balle-Flygare-type FTMW spectrometer used in these experiments has been described elsewhere, [39][40][41][42] so only a brief description is provided here; a more extensive discussion can be found in the Supporting Information. Subsequent work with several substituted oxycarbenes indicates that the propensity for tunneling is greatly influenced by the identity of the substituent.…”
Section: Oomentioning
confidence: 99%
See 1 more Smart Citation
“…[24,25] More recently, Schreiner et al reported the generation of trans,trans-and trans,cis-HO À C À OH by the thermal extrusion of CO 2 from oxalic acid and its subsequent isolation in an argon matrix at 10 K. [23] A similar experiment showed that hydroxycarbene (HÀC ÀOH) rapidly isomerizes to formaldehyde (CH 2 O) at 10 K, a phenomenon attributed to quantum tunneling through the 125 kJ mol À1 ÀOH, with the CCSD(T)/cc-pVTZ relative energies calculated by Schreiner et al [23] barrier. The 5-43 GHz Balle-Flygare-type FTMW spectrometer used in these experiments has been described elsewhere, [39][40][41][42] so only a brief description is provided here; a more extensive discussion can be found in the Supporting Information. Subsequent work with several substituted oxycarbenes indicates that the propensity for tunneling is greatly influenced by the identity of the substituent.…”
Section: Oomentioning
confidence: 99%
“…[6,26] In contrast, HOÀC ÀOH displays no tunneling behavior and is stable under the low-temperature matrix conditions. [42][43][44][45] Sample FTMW and DR spectra are shown in Figure 2. [7,27,37,38] We present here the first direct gas-phase evidence for trans,cis-HOÀC ÀOH, and a precise determination of its rotational spectrum and geometric structure, using a combination of Fourier transform microwave spectroscopy (FTMW), microwave-millimeter-wave double resonance (DR) spectroscopy, and high-level theoretical calculations.…”
Section: Oomentioning
confidence: 99%
“…The revealed multiconfiguration nature of the wave function for HOOO • and its unusual structure suggest that both the static and the dynamic electronic correlations should be considered in order to obtain an adequate result. In a recent paper, the molecular structure of HOOO • was studied again using isotopic FTMW spectroscopy and double-resonance technique 66 . The hydrotrioxy radical was generated by an electric discharge in an H 2 O/O 2 or H 2 /O 2 mixture in an inert gas mixture.…”
Section: B Hooo • Structurementioning
confidence: 99%
“…The most extreme case is the HOOO radical whose enthalpy of formation was not established until 2010 . The infrared spectra of cis and trans HOOO was extremely difficult to observe, and the determination of equilibrium structure is even more challenging . However, the importance of HOOO in solution and atmospheric chemistry elicited important experimental and theoretical advances that improved our understanding of the chemistry of HOOO.…”
Section: Introductionmentioning
confidence: 99%